2019
DOI: 10.1007/s00394-019-01993-8
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical inflammation, telomere shortening, homocysteine, vitamin B6, and mortality: the Ludwigshafen Risk and Cardiovascular Health Study

Abstract: Purpose Short telomeres and B vitamin deficiencies have been proposed as risk factors for age-related diseases and mortality that interact through oxidative stress and inflammation. However, available data to support this concept are insufficient. We aimed to investigate the predictive role of B vitamins and homocysteine (HCY) for mortality in cardiovascular patients. We explored potential relationships between HCY, B vitamins, relative telomere length (RTL), and indices of inflammation. Methods Vitamin B6, HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 44 publications
5
53
0
Order By: Relevance
“…While some studies reported an inverse association between telomere length and HCY [ 62 , 94 , 95 ], others did not [ 63 , 96 , 97 ]. In the prospective LURIC study, plasma HCY was identified as an independent predictor of all-cause mortality [ 66 ]. The unadjusted HR for death from all causes and from CVD was nearly three times higher in the fourth quartile of HCY than in the first quartile.…”
Section: B-vitamins Homocysteine Telomere Length and Cvdmentioning
confidence: 99%
“…While some studies reported an inverse association between telomere length and HCY [ 62 , 94 , 95 ], others did not [ 63 , 96 , 97 ]. In the prospective LURIC study, plasma HCY was identified as an independent predictor of all-cause mortality [ 66 ]. The unadjusted HR for death from all causes and from CVD was nearly three times higher in the fourth quartile of HCY than in the first quartile.…”
Section: B-vitamins Homocysteine Telomere Length and Cvdmentioning
confidence: 99%
“…[13] Raised serum homocysteine is an independent risk factor for cardiovascular diseases [13,15,18]. Elevated serum homocysteine is associated with a rise in morbidity and mortality [18,19].…”
Section: Homocysteinementioning
confidence: 99%
“…An increase in serum homocysteine results in oxidative stress and systemic inflammation which in turn leads to an accelerated telomere shortening [13,19]. Furthermore, elevated serum homocysteine damages endothelial cells [13].…”
Section: Homocysteinementioning
confidence: 99%
“…Solid knowledge about the factors that influence RTL is important for a potential clinical use of this promising marker and an appropriate interpretation of results. Lifestyle factors, such as physical activity, nutrition and stress have been suggested as potential modulators of telomere length [3][4][5][6][7][8][9][10][11] . For example, regular endurance exercise induces telomerase, an enzyme that can prolong telomeres, and thus prevent telomere shortening [4][5][6][7] .…”
mentioning
confidence: 99%
“…Nutritional factors also appear to be involved in telomere biology. Pusceddu et al have shown that vitamin B6, B12 and homocysteine relate to RTL and mortality in cardiovascular patients 11 . In contrast, in longitudinal studies various diets or food supplements, considered generally healthy have shown little or no effect on telomere attrition 8,9 . Obesity is a very common condition in Western societies that is associated with a broad range of metabolic alterations, elevated oxidative stress and chronic low-grade inflammation 10,12 .…”
mentioning
confidence: 99%